THE EFFECT OF CUSTOMER SATISFACTION, BARRIERS TO SWITCHING, AND CUSTOMER TRUST ON CUSTOMER RETENTION AT HERDACAKE BAKERY, PUGER JEMBER DISTRICT - Amelia, Rita; Supeni, Retno Endah; Setianingsih, Wahyu Eko (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of customer satisfaction, switching barriers and customer trust on customer retention at the Herdacake bakery, Puger district, Jemeber. This type of research uses descriptive quantitative research. The analytical method in this research is multiple linear regression analysis, the population in this research is the customers of the Herdacake bakery. The sample used was 160 respondents. The results of this research show that this conclusion is proven (1) the customer satisfaction variable has a positive and significant effect on customer retention. With a t count of 9.378 and a significance level of 0.00. (2) the switching barrier variable has a positive and significant effect on customer retention. With a t count of 2.833 and a significance level of 0.00. (3) the customer trust variable has a positive and significant effect on customer retention. With a t count of 3.915 and a significance level of 0.03. The variables Customer Satisfaction, Switching Barriers, and Customer Trust simultaneously have a positive and significant effect on customer retention in herdacake bakery.